2005
DOI: 10.1287/mnsc.1050.0417
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Conservatism and Managerial Incentives

Abstract: T here are two sources of agency costs under moral hazard: (1) distortions in incentive contracts and (2) implementation of suboptimal decisions. In the accounting literature, the relation between conservative accounting and agency costs of type (1) has received considerable attention (cf. Watts 2002). However, little appears to be known about the effects of accounting conservatism on agency costs of type (2) or trade-offs between agency costs of types (1) and (2). The purpose of this study is to examine this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…So, for example, Kwon et al (2001) model accounting conservatism in a principal agency context and conclude that, in a limited liability context, the optimal accounting system will always be conservative, 9 and show that conservatism has no role in an unlimited liability context. Kwon (2005) studies a more general principal agent model that focuses on the effect of conservative accounting on the agency costs of the agent's suboptimal effort choice under moral hazard. His results show that there are logically possible worlds where conservatism can be beneficial, and logically possible worlds where conservatism may be harmful.…”
Section: Stewardship and Managerial Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…So, for example, Kwon et al (2001) model accounting conservatism in a principal agency context and conclude that, in a limited liability context, the optimal accounting system will always be conservative, 9 and show that conservatism has no role in an unlimited liability context. Kwon (2005) studies a more general principal agent model that focuses on the effect of conservative accounting on the agency costs of the agent's suboptimal effort choice under moral hazard. His results show that there are logically possible worlds where conservatism can be beneficial, and logically possible worlds where conservatism may be harmful.…”
Section: Stewardship and Managerial Monitoringmentioning
confidence: 99%
“…His results show that there are logically possible worlds where conservatism can be beneficial, and logically possible worlds where conservatism may be harmful. Balakrishnan et al (2013) extend the work of Kwon (2005). Their basic model, which focuses on the effort motivation role, finds that the optimal level of conservatism varies with the acuteness of the agency problem.…”
Section: Stewardship and Managerial Monitoringmentioning
confidence: 99%
“…Additionally, prior studies suggested that conservatism limits the opportunistic behavior of managers (Brown, He &Teitel, 2006;Chen, Hemmer & Zhang, 2007;Watts, 2003a) and decreases information asymmetry among outside shareholders and managers (LaFond& Watts, 2008). Moreover, conservatism is more beneficial in monitoring the cost of suboptimal managerial decisions than if the earnings were measured liberally or neutrally (Kwon, 2005). The usefulness of conservatism in the agency relationship, ultimately enhance the usefulness of financial reports (Ball & Shivakumar, 2006) and improve firm value (Watts, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…k l þ d h (yielding LR 1 (m) = 0), to fully exploit the moving support feature of the distribution. This notion that moral hazard considerations can justify conservative biases (given LL) is similar in spirit to that in Kwon et al 2001 andKwon 2005. In our setup, another consideration arises because the information system is also used for the principal's decision-making purpose. Thus the optimal cutoff weighs the desire for conservatism (m large) driven by moral hazard concerns and the desire for unbiasedness (m equal to k h ) dictated by decisionmaking concerns.…”
Section: Benchmark 1: Optimal System Without Moral Hazardmentioning
confidence: 77%
“…1 We distinguish two types of stewardship uses of accounting information: one is to motivate the (standard) managerial efforts that affect the first moment (mean) of the firm output, and the other is to motivate the managerial efforts that facilitate the principal's decision making by affecting the second moment of the firm output (we refer to such efforts as the decision-facilitating efforts). We find that, while conservative bias may be optimal when accounting information is used only to motivate mean-increasing efforts (Kwon, Newman, and Suh 2001;Kwon 2005), liberal bias is necessary when decision making and control interact in the sense that accounting information is also used to motivate decision-facilitating efforts.…”
Section: Introductionmentioning
confidence: 94%